Plasma apolipoprotein concentrations and incident diabetes in subjects with prediabetes - Mikaël Croyal; Matthieu Wargny; Kevin Chemello; Chloé Chevalier; Valentin Blanchard; Edith Bigot-Corbel; Gilles Lambert; Cédric Le May; Samy Hadjadj; Bertrand Cariou (Cardiovascular Diabetology, 2022)
Abstract Background The identification of circulating biomarkers associated with the risk of type 2 diabetes (T2D) is useful for improving the current prevention strategies in the most at-risk patients. Here, we aimed to investigate the association of plasma apolipoprotein concentrations in prediabetes subjects with the incidence of new-onset T2D during follow-up. Methods In the IT-DIAB prospective study, 307 participants with impaired fasting glucose levels (fasting plasma glucose [FPG]: 110–125 mg/dL) were followed yearly for 5 years. The onset of T2D was defined as a first FPG value ≥ 126 mg/dL during follow-up. Apolipoprotein (apo)A-I, A-II, A-IV, B100, C-I, C-II, C-III, C-IV, D, E, F, H, J, L1, M, and (a) plasma concentrations were determined by mass spectrometry. Correlations between apolipoproteins and metabolic parameters at baseline were assessed by Spearman’s coefficients. Kaplan–Meier curves were drawn using a ternary approach based on terciles and incident T2D. The association between plasma apolipoproteins concentrations and the incidence of T2D was determined using Cox proportional-hazards models. Results During a median follow-up of 5-year, 115 participants (37.5%) developed T2D. After adjustment for age, sex, body mass index, FPG, HbA1c, and statin use, the plasma levels of apoC-I, apoC-II, apoC-III, apoE, apoF, apoH, apoJ, and apoL1 were positively associated with a high risk for T2D. After further adjustment for plasma triglycerides, only apoE (1 SD natural-log-transformed hazard ratio: 1.28 [95% confidence interval: 1.06; 1.54]; p = 0.010), apoF (1.22 [1.01; 1.48]; p = 0.037), apoJ (1.24 [1.03; 1.49]; p = 0.024), and apoL1 (1.26 [1.05; 1.52]; p = 0.014) remained significantly associated with the onset of T2D. Kaplan–Meier survival curves also showed that the lower third of plasma apoE levels (< 5.97 mg/dL) was significantly associated with a lower risk of conversion to T2D (log-rank test, p = 0.002) compared to the middle and upper thirds. Conclusions The plasma apoE levels are positively associated with the risk of T2D in prediabetes subjects, independently of traditional risk factors. The possible associations of apoF, apoJ, and apoL1 with T2D risk also pave the way for further investigations. Trial registration This trial was registered at clinicaltrials.gov as NCT01218061 and NCT01432509